THE FAILURE OF UNITED NATIONS FORCES (UNAMIR) TO STOP TUTSI GENOCIDE IN RWANDA DURING 1994 - Nduwayezu Didas (2016)
This study is about describing the causes of the failure of United Nations forces (UNAMIR) to stop the Tutsi genocide in Rwanda during 1994, the case study was the tutsi genocide in Rwanda .the Specific objectives of this study were to identify origin of ethnic groups in Rwanda and the causes of the 1994 Tutsi genocide, to describe the military intervention of United Nations Assistance Mission for Rwanda (UNAMIR) to stop the Tutsi genocide in Rwanda and to identify the factors which contributed to the failure of United Nations Assistance Mission for Rwanda (UNAMIR) to stop Tutsi genocide. Research question was why United Nations forces (UNAMIR) failed to stop the Tutsi genocide in Rwanda during 1994. The researcher was pushed by the fact that most of United Nations peacekeeping missions in world fail and he was interested in finding the causes of the failure of those peacekeeping missions and at the end of the researcher gave useful recommendations. Rwanda genocide was chosen as a case study to determine the failure of United Nations peacekeeping mission and the related research has been conducted by Rwanda government before. Different books, web sites, journals and reports related to the failure of United Nations in peacekeeping missions in the world have been consulted in literature review and Descriptive research design was used. The findings revealed that the main reasons behind the failure of the United Nations forces (UNAMIR) in stopping Tutsi genocide in Rwanda during 1994 are: Lack of political will of dominant Member States of United Nations (UN) to intervene , inadequate financial resources and mission’s poor design .The researcher concluded that the UN really failed to take immediate action and strengthen UNAMIR to stop the massacres, due to opposition from dominant member states such as France , USA and UK and he recommended that The United Nations and its member states must be prepared to mobilize political will to act in the face of gross violations of human rights which have not reached the ultimate level of a genocide and the UN Secretary- General should initiate an action plan to prevent genocide involving the whole UN system and aiming to provide input to the World Conference against Racism ,Racial Discrimination, Xenophobia and Related Intolerance .